THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND INTELLIGENCE ON PROBLEM-SOLVING SKILLS : Case Study of Grade XI Students at SMAN 1 Cilograng - Supriyadi Supriyadi; Aris Subranta; Novi Nurfadilah (Indonesian of Interdisciplinary Journal, 2025)
This research aims to analyze the influence of emotional intelligence and intelligence on the problem-solving abilities of class XI students at SMAN 1 Cilograng. This research uses a multiple regression analysis test method, which aims to determine whether there is a positive or negative influence from all independent variables (X) on the dependent (Y). The population in this study was class XI students at SMAN 1 Cilograng, totaling 310 students, and the sample used was 76 students. This research is a quantitative research type with a descriptive approach. Data collection in this research used a questionnaire instrument as a data collection tool consisting of indicators for each variable. To process data using the SPSS Version 25.0 computerized system. Based on the research results, it can be concluded that there is a significant influence of emotional intelligence (X1) on problem-solving ability (Y) with a t-count of 4.533 > t-table 1.666 and a significance of 0.000 < 0.05. Meanwhile, intelligence (X2) also has a significant effect on problem-solving ability (Y) with a t-count of 3.695 > t-table 1.666 and a significance of 0.000 < 0.05. and it can also be concluded that there is a significant or simultaneous influence between the influence of emotional intelligence and intelligence on the problem-solving abilities of the case study of class